Does Board Gender Diversity Moderate ESG, Dividend Policy, and Firm Value Relationships? - Nur Aisyah, Fara Sahira; Haryati, Tantina; Vendy, Vicky (Program Studi Akuntansi FPEB UPI, 2024)
The objective from this study is to investigate the relationship from ESG performance and dividend policy on firm value, and the impact of moderating variable that from board gender diversity. The sample comprises 103 manufacturing companies registered on the IDX in both 2021 and 2022. Data were gathered from annual and sustainability reports and analyzed by panel data regression. The research findings show that environmental performance and dividend policy have a positive effect on firm value. Combined ESG, social, and governance performance have no influence on firm value. On the other hand, board gender diversity can negatively moderate the effect of dividend policy on firm value, but it cannot moderate the influence from combined ESG performance on firm value.